1991
DOI: 10.3233/ves-1991-1307
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Horizontal Head and Trunk Rotation in Patients with Loss of Vestibular Functions

Abstract: In patients with loss of vestibular functions, we studied psychophysically the self-motion perception for ‘trunk in space’ and ‘head in space’ during various combinations of horizontal head and trunk rotation in the dark. The results were compared to those of normal subjects. For their ‘trunk in space’ perception, the subjects relied on their internal image of space, derived from the vestibular receptors in the head, and referred their trunk to this as a reference by adding to it a nuchal trunk-to-head signal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…This has striking similarities to Bierbrauer and colleagues who found that a path integration deficit in APOE ε4 carriers emerges only if external visual cues are not available [ 20 ]. These findings are also consistent with limited studies that show path integration impairment in vestibular deficient humans emerges when external cues are not available [ 38 ], supporting the emerging theory that vestibular function plays a mechanistic role in path integration deficits previously observed in adults at-genetic-risk AD.…”
Section: Discussionsupporting
confidence: 89%
“…This has striking similarities to Bierbrauer and colleagues who found that a path integration deficit in APOE ε4 carriers emerges only if external visual cues are not available [ 20 ]. These findings are also consistent with limited studies that show path integration impairment in vestibular deficient humans emerges when external cues are not available [ 38 ], supporting the emerging theory that vestibular function plays a mechanistic role in path integration deficits previously observed in adults at-genetic-risk AD.…”
Section: Discussionsupporting
confidence: 89%
“…This has striking similarities to Bierbrauer and colleagues who found that a path integration deficit in APOE ε4 carriers emerges only if external visual cues are not available 4 . These findings are also consistent with limited studies that show path integration impairment in vestibular deficient humans emerges when external cues are not available 19 , supporting the emerging theory that vestibular function plays a mechanistic role in path integration deficits previously observed in adults at-genetic-risk AD.…”
Section: Discussionsupporting
confidence: 89%